Vitamin D and foot and ankle trauma: An individual or societal problem. (June 2019) - Ribbans, William J.; Aujla, Randeep S.; Ashour, Rami; Allen, Patricia E.; Wood, Edward V.
Highlights: Mean vitamin D levels were 52.0 nol/L with a standard deviation of 28.5 nmol/L. Only 19% of patients had normal vitamin D levels. 23% were grossly deficient. Age, gender, anatomical location and injury type did not affect vitamin D levels. Abstract: Background: Vitamin D deficiency is a worldwide health concern. Hypovitaminosis D may adversely affect recovery from bone injury. The authors aimed to perform an audit of the Vitamin D status of patients in three centres in the United Kingdom presenting with foot and ankle osseous damage. Methods: Serum 25-hydroxyvitamin-D (vitamin D) levels were obtained in patients presenting with imaging confirmed foot and ankle osseous trauma. Variables including age, gender, ethnicity, location, season, month, anatomical location and type of bone injury were recorded. Results: 308 patients were included from three different centres. 66.6% were female. The average age was 47.7 (range; 10–85). The mean hydroxyvitamin-D levels were 52.0 nmol/L (SD 28.5). 18.8% were grossly deficient, 23.7% deficient, 34.7% insufficient and 22.7% within normal range. 351 separate bone injuries were identified of which 104 were categorised as stress reactions, 134 as stress fractures, 105 as fractures and 8 non-unions. Age, gender, anatomical location and fracture type did not statistically affect vitamin D levels. Ethnicity did affect Vitamin D levels: non-Caucasians mean levels were 32.4 nmols/L compared to Caucasian levels of 53.2 nmol/L (p = 0.0026). Conclusion: Only 18.8% of our trauma patients had a normal Vitamin D level and 22.7% were grossly deficient. Patient age, gender, anatomical location and injury type did not statistically affect vitamin D levels. No difference between trauma and elective patients were found. Hypovitaminosis D is a problem of society in general rather than specific to certain foot and ankle injury patterns or particular patient groups sustaining trauma. Level of evidence: 2b.